Are caste categories misleading? The relationship between gender and jati in three Indian states - Shareen Joshi; Nishtha Kochhar; Vijayendra Rao (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
This paper examines the relationship between caste and gender inequality in three states in India. When households are grouped using conventional, government-defined categories of caste we find patterns that are consistent with existing literature: lower-caste women are more likely to participate in the labour market, have greater decision-making autonomy within their households, and experience greater freedom of movement. When households are grouped by the narrower sub-caste categories of jati, where caste is lived and experienced, we find that the relationships are far more varied and nuanced. These results suggest that focusing on broad caste categories such as 'scheduled castes' and 'scheduled tribes' can be misleading for an understanding of the relationship between caste and gender, and for the targeting of anti-poverty programmes.
Keywords: I3; J4; O1; 330; autonomy; caste; gender; India; jati; labour force participation